Root hemiparasitic plants are associated with high diversity in temperate grasslands. (2nd November 2016) - Fibich, Pavel; Lepš, Jan; Chytrý, Milan; Těšitel, Jakub
Abstract: Questions: Is the incidence of root hemiparasitic plants in non‐forest vegetation associated with high diversity? Are root hemiparasites more associated with species‐rich vegetation than other species? Location: Czech Republic. Methods: Plot size‐corrected species richness, Shannon diversity and Pielou's evenness were computed for a representative set of 18 101 vegetation plots representing all main types of terrestrial open (non‐forest) habitats of the country. Null models of species richness assuming occurrence of a random species with given occurrence frequency, reflecting higher incidence probability in species‐rich plots, were constructed for 16 common root hemiparasitic species. The null model distribution of species richness was subsequently compared with the actual mean species richness of plots containing the respective root hemiparasites. Median values of plot Shannon diversity and evenness were computed for each species in the database. Values obtained for plots containing individual root hemiparasites were compared with distribution of values for other species in the database. Results: The occurrence of 11 of 16 root hemiparasites studied was associated with high species richness significantly more than under random expectations; three species were negatively associated. Three root hemiparasites were among the top 5% of all species associated with high species richness and Shannon diversity, and eight were among the top 25%. Almost 50% of the top 1% most species‐rich plots contained at least one root hemiparasitic species. Conclusions: We demonstrated a positive association between the incidence of most root hemiparasites and diversity of non‐forest terrestrial plant communities at a broad landscape scale. This finding scales up the results of experimental studies that showed some root hemiparasites act as ecosystem engineers, increasing vegetation diversity. Root hemiparasites should be regarded as important biodiversity indicators and potential drivers of biodiversity. As such, conserving their wild populations or promoting their establishment should become a goal of nature conservation and ecological restoration. Abstract : An exploration of a large vegetation database of non‐forest plant communities identified a positive association between high local species diversity and presence of root‐hemiparasitic species on a broader landscape scale. Therefore, root hemiparasites should be regarded as important biodiversity indicators and potential biodiversity drivers.